Comparative analysis of selected biomechanic characteristics between a support backward swing and sport swing for the 1¼ straddle-piked forward salto on the parallel bars - Kolar, E.; Kolar, K. A.; Stuhec, S. (Sports Biomechanics, 2002)
The aim of the research was to study the relationships between performance variables in a support backward swing (SBS) which was used as a progressive step in the learning procedure for a 1¼ straddle-piked front somersault and the swing prior to a 1¼ straddle-piked front somersault from support to bent arm support on the parallel bars (5/4S). Mitjia Petkovšek, parallel bars gold medallist at the 2000 EC in Bremen, performed these elements. Kinematic analysis involved CMAS software (Praha, 1993), and the Suskana body segment model that has 17 points and 15 segments. Kinetic variables were estimated using 2D IMGIM software, which has 8 points and 6 segments (Colja and Cuk, 1994). The results indicated that some kinetic aspects of the two types of swings were similar but there were important differences in kinetic aspects of the motion. During the swing for the 5/4S, force and torque were higher than in the SBS.